87 Mapping disease severity and progression of renal involvement in patients with systemic lupus erythematosus. (April 2019) - Amelio, Justyna; Gairy, Kerry; Mahajan, Anadi; Kaur, Gavneet; Bass, Damon; Levy, Rodger; Roth, David
Abstract : Background: Despite recent advances in the treatment of systemic lupus erythematosus (SLE) and lupus nephritis (LN), understanding of their pathogenesis and the interrelation between disease states remains incomplete. A pragmatic review (GSK study LS3178) was conducted to map disease severity and progression of renal involvement in SLE, focusing on: LN development among patients with SLE, within-LN progression, and progression to end-stage renal disease (ESRD). Methods: A keyword based literature search was conducted using PubMed, Google and Google Scholar and supplemented with a bibliography search relevant to the focus area. The following publications were screened and prioritized for inclusion: high quality; published after 2010; addressed a topic of focus or an information gap; data were from the USA or Europe. High-quality pre-2010 and non-USA/Europe publications were permitted. Results: Overall, 248 citations were identified (keyword based search, n=117; bibliography search, n=131). Following full text screening, 144 publications were considered relevant to the review and 26 were selected for inclusion (21 primary studies, 3 narrative reviews and 2 systematic literature reviews). An overview of the results is provided in the Figure. This review identified that 726% of patients had LN at the time of SLE diagnosis, and 3148% of patients with SLE developed LN in the disease course, most (8090%) within 5 years of diagnosis. Class IV nephritis was the most common LN class found at first (3560%) and repeat (3563%) biopsy and had the worst prognosis. Histological transformation from one LN class to another was reported in 4076% of patients, most commonly in patients with nonproliferative lesions in the first biopsy. Overall, the proportion of patients who subsequently developed ESRD was 36% (SLE) and 428% (LN). Limited data existed for time to progression within LN and from SLE/LN to ESRD, and for renal signs present before LN diagnosis. Conclusions: This review highlights risk factors for developing LN and progressing from SLE/LN to ESRD. Male patients, patients of non white ethnicities, and patients of a younger age at SLE diagnosis had the highest risk for developing LN and progressing from SLE/LN to ESRD. Of the renal parameters, elevated serum creatinine was identified as the best predictor of worsening disease state. A higher risk of worse outcomes is seen in the earlier SLE/LN disease stages, demonstrating the importance of early diagnosis and the need for effective disease modifying treatments for SLE and LN. Funding Source(s): Study funded by GSK.